Al-kharaj Bi Al-dhaman Mengenai Pembagian Hadiah Mev di Jitosol - Lia Indah Khilmina; Nurifa Laksmitasari Azizah (STAI Al Musaddadiyah Garut, 2026)
This study analyzes the validity of Maximal Extractable Value (MEV) reward distribution within the JitoSOL Liquid Staking protocol on the Solana network through the perspective of the Islamic legal maxim Al-Kharaj bi al-Dhaman. Amidst the rapid adoption of crypto assets in 2026, Jito introduced an innovation in additional profit distribution for token holders through transaction sequence optimization. However, this mechanism has sparked debate regarding the fairness of revenue sources and the proportionality of risks borne by investors. Employing a normative-juridical research method with an usuliyyah approach, this research examines whether Maximal Extractable Value yields are categorized as legitimate business returns (Kharaj) or prohibited market manipulation practices (Najasy). The results indicate that MEV distribution in JitoSOL can align with the Al-Kharaj bi al-Dhaman principle as long as investors bear systemic loss and slashing risks. Nevertheless, a critical point lies in the transparency of the MEV source; if it originates from strategies that harm other users (such as front-running), the element of blessing (barakah) is lost. This study concludes the necessity of sharia governance standardization for digital reward distribution algorithms. Keywords: Al-Kharaj bi al-Dhaman, MEV Reward, JitoSOL, Solana, Liquid Staking.